An Accident Analysis during the Covid-19 Pandemic in Indonesia uses the Accident Rate Method - Rahmawati, Roselina; Mukhlisin, M; Fatmawati, Leily; Wiyana, Yustinus Eka; Wicaksono, Teguh Mulyo (Jurnal Teknik Sipil, 2024)
Abstract Land transportation traffic accidents in Indonesia were affected by the Covid-19 pandemic. During the Covid-19 pandemic, several transportation policies were implemented. An absolute must for implementing transportation safety. During the Covid pandemic in 2019 and 2020, the average number of traffic accidents was 25%, the number of fatalities was 24%, the number of injured victims was 21% and the number of accidents was 25%. In 2021, Indonesian people will begin to face new normal conditions, where all activities run normally in line with the presence of the Covid 19 virus. So that in 2021 and 2022 there will be another increase in the number of traffic accidents, deaths, injuries and accidents. The average figures for 2021 and 2022 for the number of traffic accidents are 26%, the number of fatalities is 26%, the number of injured victims is 23% and the number of accidents is 28%. With the presence of Regulation Number 21 of 2020 concerning PSBB, the number of accidents in Indonesia can be reduced, but the reduction in the accident rate has not occurred significantly. In 2019 the accident rate was 31% and in the year the PSBB policy was implemented the accident rate was 23%, the reduction in the accident rate was only 8%. Keywords : Accident rate, covid 19 pandemic, descriptive analysis, road traffic accidents